Pembuatan dan Pengesahan Perjanjian Perkawinan Melalui Penetapan Pengadilan dan Notaris Pasca Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Timex, Hеndhy; Suhariningsih, Suhariningsih; Sulіstyаrіnі, Rаchmі (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This article aims to examine the issuance marriage agreement based on the Decision of Constitutional Court Number 69 / PUU-XІІІ / 2015. This study is a normative research with statute and cases approach. The Decision of Constitutional Court Number 69 / PUU-XІІІ / 2015 provides that the marriage agreement which has been made either through a court or notary request must still be recorded and passed to the Population and Civil Registry Office. It aims to provide legal certainty and legal protection for every side.